The Study on Acute.Subacute Toxicity and Anti-cancer Effect of H Herbal-acupuncture - Tae-Hui Kim; Ki-Rok Kwon; Seon-Goo Lee (Korean Pharmacopuncture Institute, 2002)
Objectives : The purpose of this study is to investigate Acute and Subacute Toxicity, and Anti-cancer Effect of H Herbal-acupuncture on mice and rats. Methods : Balb/c mice were injected intraperitoneally with H Herbal-acupuncture for LD50 and acute toxicity test. Sprague-Dawley rats were experimented in the same way for subacute toxicity test. H Herbal-acupuncture was injected into abdomen of mice having S-180 cancer cell line. Result : 1. During the test, LD50 could not be counted since there was no expired subjects. 2. In an acute toxicity test, the loss of motility and reflex action was observed, but weight increased in the treatment group, compared with those in the normal group (P<0.05). 3. In an acute toxicity test of serum biochemical values of mice, glucose increased in the treatment group II while total cholesterol was increased in the all treatment groups (P<0.05). 4. In a subacute toxicity test, a little loss of motility and reflex action was observed in the treatment group. Weight of mice in the treatment group decreased on the 28th day. 5. In a subacute toxicity test, liver weight was decreased but lung weight of mice increased in the all treatment groups (P<0.05). 6. As a result of measuring Complete Blood Count test (CBC) of rat, HCT was decreased in treatments even though it was not significant, compared with the normal group (P<0.05). 7. In a serum biochemical value test of subacute toxicity, total protein and albumin decreased in the all treatment groups. Creatinine, glucose, GOT increased in the treatment group I compared with the control group. Alkaline phos-phatase decreased in treatment II group, compared with the control group (P<0.05). 8. Median survival time that was measured in the rats treated with sarcoma-180 cancer cell Median decreased in the treatment group, compared with the control group (P<0.05). 9. Natural killer cell activity showed significant reduction at 100:1 and 10:1 E/T ratio while it increased at 50:1 E/T ratio. It is inferred that there was an error in the experiment (P<0.05). 10. In an interleukin-2 productivity test, even though it decreased in lung cancer, and increased in abdomen cancer, but it was only a small difference (P<0.005). 11. After injecting B16F10 cell into a capillary vessel of C57BL/6 mice and generating metastasized lung cancer, the lung was examined with the naked eye. It was not possible to see metastasized cancer in the all groups on the seventh day but the cancer was viewed on the fourteenth day. The number and volume of metastasized cancer in the treatment group enlarged in the treatment group, compared with the control group. Conclusion : According to the results, H herbal-acupuncture took no effects in cancer.